Control of lettuce big‐vein disease by application of fungicides and crop covers. (11th February 2019) - Opatovsky, I.; Elbaz, M.; Dori, I.; Avraham, L.; Mordechai‐Lebiush, S.; Dombrovsky, A.; Tsror (Lahkim), L.
Abstract : One of the economically important diseases of lettuce is lettuce big‐vein disease (LBVD), which leads to severe yield losses. LBVD is associated with a complex of two viruses, Lettuce big‐vein associated virus (LBVaV) and Mirafiori lettuce big‐vein virus (MLBVV). These viruses are transmitted by motile zoospores of Olpidium spp. fungi, which persist in the soil for decades through resting spores. In greenhouse and field experiments, this study tested whether changing plant and soil temperatures together with fungicide application would have a significant effect on controlling LBVD in lettuce. Soil fumigation with metam sodium was not effective at controlling the disease, as opposed to treatment with chloropicrin and methyl bromide. Moreover, the fungicides carbendazim and fluazinam were effective in reducing the incidence of Olpidium virulentus . Nevertheless, control of the fungal vector did not seem to be sufficient to control the disease due to the transition ability of the virus under low vector abundance. Crop covers, which affect the favourable environmental conditions for the viruses by lowering soil temperature and raising air temperature, reduced the disease symptoms. Combining fungicides with crop cover had a synergistic effect on reducing disease symptoms, thus providing a sustainable solution for LBVD.